2019
DOI: 10.3390/rel10070429
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Religious Literacy in Pakistani Education

Abstract: Religious education is a compulsory subject in Pakistani schools in which students learn basic knowledge about Islam without exploring the sectarian differences between each sect of Islam. The division of Muslims into Sunni and Shia and the further division of Sunni Muslims into different sects has caused massive sectarian violence in Pakistan. This study uses qualitative methods to explore the possibility of engaging with religious literacy and religious education to explain the purpose, contents, and practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 18 publications
3
15
0
2
Order By: Relevance
“…The findings of the present study revealed that madrasas' education has a significant role in sectarian violence. These findings are closely in line with the recent study conducted by Ashraf (2019) who explored the misinterpretation of Islamic education by each sect as a cause of the upsurge of sectarian violence in Pakistan. Similarly, Waseem et al (2010) narrated that sectarian conflicts are accelerated by clergymen and the main ambitions behind this are the achievements of the economic and political goals rather than religious ideologies.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of the present study revealed that madrasas' education has a significant role in sectarian violence. These findings are closely in line with the recent study conducted by Ashraf (2019) who explored the misinterpretation of Islamic education by each sect as a cause of the upsurge of sectarian violence in Pakistan. Similarly, Waseem et al (2010) narrated that sectarian conflicts are accelerated by clergymen and the main ambitions behind this are the achievements of the economic and political goals rather than religious ideologies.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of this research agree with those of studies that showed that citizenship education is perceived differently within the Pakistani education system, wherein Islam remains the central point of discussion (Ahmad 2004;Ashraf 2019;Lall 2012). This study adds to the knowledge that religious education settings can lead to sectarianism and intolerance towards other religious groups, and teachers in this sector consider Islam as the only form of GCE.…”
Section: Discussionsupporting
confidence: 90%
“…However, this type of male contention is turned down by McCormack, Nettel-Aguirre, Hawe, & Doyle-Baker (2017) who have confirmed that the effect upon female features has directly been associated with the hormonal changes in the body of females, not by participation in sports or anything else. The present study has affirmed that the parental role plays a very positive and encouraging role particularly in connection with girls' participation in sports and this finding is endorsed by Ashraf (2019) who claims that parental attitude has a very positive influence on girls' participation in sports.…”
Section: Discussionsupporting
confidence: 79%